Cell Adhesion Molecules Involved in Neurodevelopmental Pathways Implicated in 3p-Deletion Syndrome and Autism Spectrum Disorder - Gandawijaya, Josan; Bamford, Rosemary A.; Burbach, J. Peter H.; Oguro-Ando, Asami (Frontiers in Cellular Neuroscience, 2021)
Autism spectrum disorder (ASD) is characterized by impaired social interaction, language delay and repetitive or restrictive behaviors. With increasing prevalence, ASD is currently estimated to affect 0.5-2.0% of the global population. However, its etiology remains unclear due to high genetic and phenotypic heterogeneity. Copy number variations (CNVs) are implicated in several forms of syndromic ASD and have been demonstrated to contribute towards ASD development by altering gene dosage and expression. Increasing evidence points towards the p-arm of chromosome 3 (chromosome 3p) as an ASD risk locus. Deletions occurring at chromosome 3p result in 3p-deletion syndrome (Del3p), a rare genetic disorder characterized by developmental delay, intellectual disability, facial dysmorphisms and often, ASD or ASD-associated behaviors. Therefore, we hypothesize that overlapping molecular mechanisms underlie the pathogenesis of Del3p and ASD. To investigate which genes encoded in chromosome 3p could contribute towards Del3p and ASD, we performed a comprehensive literature review and collated reports investigating the phenotypes of individuals with chromosome 3p CNVs. We observe that high frequencies of CNVs occur in the 3p26.3 region, the terminal cytoband of chromosome 3p. This suggests that CNVs disrupting genes encoded within the 3p26.3 region are likely to contribute towards the neurodevelopmental phenotypes observed in individuals affected by Del3p. The 3p26.3 region contains three consecutive genes encoding closely-related neuronal immunoglobulin cell adhesion molecules (IgCAMs): Close Homolog of L1 (CHL1), Contactin-6 (CNTN6) and Contactin-4 (CNTN4). CNVs disrupting these neuronal IgCAMs may contribute towards ASD phenotypes as they have been associated with key roles in neurodevelopment. CHL1, CNTN6 and CNTN4 have been observed to promote neurogenesis and neuronal survival, and regulate neuritogenesis and synaptic function. Furthermore, there is evidence that these neuronal IgCAMs possess overlapping interactomes and participate in common signaling pathways regulating axon guidance. Notably, mouse models deficient for these neuronal IgCAMs do not display strong deficits in axonal migration or behavioral phenotypes, which is in contrast to the pronounced defects in neuritogenesis and axon guidance observed in vitro. This suggests that when CHL1, CNTN6 or CNTN4 function is disrupted by CNVs, other neuronal IgCAMs may suppress behavioral phenotypes by compensating for the loss of function.